Impairment in natural killer cells editing of immature dendritic cells by infection with a virulent Trypanosoma cruzi population - Batalla, Estela (2013)
Early interactions between natural killer (NK) and dendritic cells (DC) shape the immune response at the frontier of innate and adaptive immunity. Activated NK cells participate in maturation or deletion of DCs that remain immature. We previously demonstrated that infection with a high virulence (HV) population of the protozoan parasite Trypanosoma cruzi downmodulates DC maturation and T-cell activation capacity. Here, we evaluated the role of NK cells in regulating the maturation level of DCs. Shortly after infection with HV T. cruzi, DCs in poor maturation status begin to accumulate in mouse spleen. Although infection induces NK cell cytotoxicity and cytokine production, NK cells from mice infected with HV T. cruzi exhibit reduced ability to lyse and fail to induce maturation of bone marrow-derived immature DCs (iDCs). NK-mediated lysis of iDCs is restored by in vitro blockade of the IL-10 receptor during NK-DC interaction or when NK cells are obtained from T. cruzi-infected IL-10 knockout mice. These results suggest that infection with a virulent T. cruzi strain alters NK cell-mediated regulation of the adaptive immune response induced by DCs. This regulatory circuit where IL-10 appears to participate might lead to parasite persistence but can also limit the induction of a vigorous tissue-damaging T-cell response.